2015
DOI: 10.1101/lm.037713.114
|View full text |Cite|
|
Sign up to set email alerts
|

Cholinergic manipulations bidirectionally regulate object memory destabilization

Abstract: Consolidated memories can become destabilized and open to modification upon retrieval. Destabilization is most reliably prompted when novel information is present during memory reactivation. We hypothesized that the neurotransmitter acetylcholine (ACh) plays an important role in novelty-induced memory destabilization because of its established involvement in new learning. Accordingly, we investigated the effects of cholinergic manipulations in rats using an object recognition paradigm that requires reactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 53 publications
10
39
0
Order By: Relevance
“…At the intracellular level, there appears to be a requirement for protein degradation at the proteasome [102, 103], protein phosphatase activity [104], CamKII [105] and nitric oxide [106, 107]. At the cell surface, there is a functional involvement of cholinergic [108] and dopaminergic receptors [109], at least for non-fear memory destabilization. Of particular relevance to fear memories are the necessity for cannabinoid CB1 receptor and calcium channel activity in the dorsal hippocampus [110] and NMDA receptor activity (specifically NR2B-containing NMDA receptors) in the basolateral amygdala [111114].…”
Section: The Reliability Of Reconsolidation Effectsmentioning
confidence: 99%
“…At the intracellular level, there appears to be a requirement for protein degradation at the proteasome [102, 103], protein phosphatase activity [104], CamKII [105] and nitric oxide [106, 107]. At the cell surface, there is a functional involvement of cholinergic [108] and dopaminergic receptors [109], at least for non-fear memory destabilization. Of particular relevance to fear memories are the necessity for cannabinoid CB1 receptor and calcium channel activity in the dorsal hippocampus [110] and NMDA receptor activity (specifically NR2B-containing NMDA receptors) in the basolateral amygdala [111114].…”
Section: The Reliability Of Reconsolidation Effectsmentioning
confidence: 99%
“…A further possibility is that nefiracetam acts though cholinergic receptors, via an elevation of extracellular acetylcholine (Sakurai et al, 1998). While cholinergic receptors have not to our knowledge been studied in relation to fear memory destabilisation, activation of muscarinic acetylcholine receptors is sufficient to enhance destabilisation of object recognition memories (Stiver et al, 2015). Moreover, it is possible that activation of nicotinic acetylcholine receptors also contributes to object memory destabilisation (Stiver et al, 2015), and so the identified action of nefiracetam to elevate acetylcholine-induced currents at nicotinic acetylcholine receptors (Oyaizu and Narahashi, 1999) may contribute to the destabilisation of cued fear memories.…”
Section: Discussionmentioning
confidence: 99%
“…While cholinergic receptors have not to our knowledge been studied in relation to fear memory destabilisation, activation of muscarinic acetylcholine receptors is sufficient to enhance destabilisation of object recognition memories (Stiver et al, 2015). Moreover, it is possible that activation of nicotinic acetylcholine receptors also contributes to object memory destabilisation (Stiver et al, 2015), and so the identified action of nefiracetam to elevate acetylcholine-induced currents at nicotinic acetylcholine receptors (Oyaizu and Narahashi, 1999) may contribute to the destabilisation of cued fear memories. However, perhaps the most likely mechanism of action is via NMDA receptors, given the effect of nefiracetam to potentiate NMDA receptor currents via interaction with the glycine binding site (Moriguchi et al, 2003), allied with the evidence that activation of NMDA receptors can facilitate destabilisation (Bustos et al, 2010;Ortiz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also use the PROMM task to investigate the neurobiological mechanisms underlying object memory updating. Previously, our group demonstrated the requirement of cholinergic signaling at M1 muscarinic receptors (mAChRs) in perirhinal cortex (PRh) for destabilization of object memories 29,30 . This effect appears to be mediated by signalling downstream of the M1 receptor, including the second messenger inositol triphosphate (IP3) and activation of the ubiquitin proteasome system (UPS), which is involved in degrading synaptic proteins and is thought to underlie destabilization at the synaptic level 14,30 .…”
Section: Introductionmentioning
confidence: 99%